Reconstruction of heel soft tissue defects using sensate medial plantar flap - Mihaela Pertea; Natalia Velenciuc; Oxana Grosu; Bogdan Veliceasa; Vladimir Poroch; Sorinel Lunca (Journal of Mind and Medical Sciences)
Introduction. Reconstruction of heel soft tissue defects represents a true challenge for any surgeon due to the particularities of this anatomical region. The tissue used to reconstruct the heel area must be resistant, innervated, and adapted to take over the body weight. Innervated medial plantar fasciocutaneous flap is one of the best solutions to cover defects at the heel level. Materials and Methods. We studied 5 patients, 4 males and one female, aged 42 to 67 years, who presented heel soft tissue defects of various etiologies. In all cases, the used reconstructive method was an insular innervated medial plantar fasciocutaneous flap. Results. Immediate and late outcomes were good. No immediate complications of necrosis type were recorded in any of the cases, and 2 years postoperatively there was no evidence of ulceration or other type of flap injury. The socio-professional reintegration of the patients was relatively rapid and their satisfaction was high. Donor area morbidity was minimal. Conclusions. Sensate medial plantar fasciocutaneous flap represents the first choice for the reconstruction of the heel soft tissue defects when patients’ local and general status allows it.